"I Took My Babies and Put Them Where They’d Be Safe": African American Women and the Continuum of Reproductive Justice Activism - Pumphrey, Shelby (Radical Teacher, 2024)
This article describes my pedagogical approach to teaching “African American Women and the History of Reproductive Justice.” It considers innovative ways to teach reproductive justice in the in Africana Studies and Women’s Studies classrooms in the contemporary moment. It highlights altar work and community collaboration as important pedagogical tools for liberatory education. The article points to various practices that both blur the lines between past and present while simultaneously transgressing traditional classroom boundaries and asking collaborators to collectively envision new reproductive futures. It highlights two projects, the Reproductive Justice Community Altar (RJCA) and Community Herbal Gathering (CHG), to highlight the utility of these transformative pedagogical tools.